The Relationship between Leadership Patterns and Job Drop- out (An applied Study on the Ministry of Justice, Aseer Region Branch) - Al- Taledy, Mufreh Jaber Mesfer; Al- Ammar, Abdullah (Journal of Economic, Administrative and Legal Sciences, 2020)
This research aimed to identify the relationship between leadership styles (Transformational, Transactional and Servant) and job dropout from. The research depends on an analytical and descriptive approach and adopted a questionnaire as a tool to collect data, and represents the study population with all employees in the Ministry of Justice in Assir region numbered (2720) employees. A random sample of (270) employees was chosen, with 10% of the study population, and the research concluded some results, and the most important of which is that there is a diversity of leadership styles used in the Ministry of Justice in Assir Region branch, and that transformational leadership, transactional leadership, and servant leadership are applied at a high level. There is no job dropout among employees in the Ministry of Justice in Assir Region branch, and there is no statistically significant relationship between leadership styles (Transformational, Transactional and Servant) and job dropout in the Ministry of Justice in Assir region branch. The research study provides a series of recommendations, the most important of which is the need for managers to build positive relationships with employees, understands their needs and fulfills their aspirations, cares about motivating them financially and morally and gives them effective means of communication, and the need for mutual trust between managers and employees to achieve the desired goals.
Keywords: leadership styles; job leakage